RANCANG BANGUN SISTEM INFORMASI KEUANGAN PADA AKADEMI KEBIDANAN SOKO TUNGGAL SEMARANG - Edy Siswanto; Iwan Koerniawan (Universitas Sains dan Teknologi Komputer, 2019)
erized Financial Administration System at the Semarang Soko Tunggal Midwifery Academy located at jl. Sendangguwo Raya no 41-42 Semarang is very useful for companies specifically in the Administration section. Especially when there are unexpected problems, but because so far the system used is still the old system and is less efficient and often errors in writing the nominal amount and also requires a long time in data processing so that makes the Administration part of the problem. With the advancement of modern technology that is the computer in an information system today is expected to provide effectiveness and efficiency in data processing and minimize the error rate in the processing system. The procedures that will be processed between SPP Payment, SPI and Practice fees using the Microsoft Visual Basic Application System and using the Microsoft Office Access database system.With the new system, it is hoped that conducting transactions in the SOKO Midwifery ACADEMY TNGGAL SEMARANG can be utilized as well as possible and used as much as possible by all groups of leaders and other employees especially the financial administration division so that it can simplify each transaction.